Negative-pressure Wound Therapy for Sacral Pressure Ulcer in Gorham-Stout Disease. Issue 1 (January 2021) - Shiokawa, Ichiro; Oshima, Naoya; Mizumura, Nao; Momosawa, Akira
Abstract : Summary: Gorham-Stout disease (GSD) is a rare musculoskeletal disorder characterized by progressive bone resorption and overgrowth of lymphatic vessels. The mechanism of GSD is still largely unknown. Negative-pressure wound therapy (NPWT) is known to accelerate wound healing and is used worldwide. Herein, we report a successful treatment of a patient with GSD having a sacral pressure ulcer, using NPWT. An 18-year-old female GSD patient was referred to our department for treating a sacral wound. The wound was disinfected by pocket incision, cleansing, and administration of antibiotics; however, the lesion remain unhealed. Histopathology of the debrided sacral wound revealed fibrous granulation tissue, with no sign of lymphatic anomalies. NPWT was started with −75 mm Hg of pressure, and neither lymphorrhea nor growth of lymphangioma was noted. Negative pressure was gradually increased to −125 mm Hg. The ulcer size decreased to 2 × 2 cm 2, which healed 3 months after hospital discharge, with no recurrence for 8 months. For progressive diseases such as GSD, NPWT may cause the regrowth of lymphangioma or other neoplasms due to an increase in vessel endothelial growth factor. NPWT appears to be one of the safest and most effective wound therapies even for this rare and difficult disease, provided the use of the following treatment protocol: Pathohistological assessment before application of NPWT, and negative pressure initially set at a low level; then, gradually increased, with careful observation to avoid lymphorrhea. When changing the foam dressing, careful checking is important to determine whether the wound is necrotic, or if there is tumor-like tissue accumulation rather than healthy granulation.